Baseline Study on the State of Devolution in the (Pre-Mandanas) Philippines - Marianne N. Juco; Ricxie B. Maddawin; Robert Hector G. Palomar; Mark Gerald C. Ruiz; Charlotte Justine Diokno Sicat (Philippine Institute for Development Studies (PIDS), 2023)
Two key recent events pushed forward the country's decentralization agenda. In 2019, the Mandanas-Garcia Supreme Court ("Mandanas") ruling increased the tax base for intergovernmental fiscal transfers in support of local governments' autonomy and revenue-raising capacity. In 2021, Executive Order No. 138 (EO 138) laid the guidelines for the effective transition of functions and responsibilities from the national to the local governments. Part of the directives in EO 138 is the design and review of devolution transition plans (DTPs). Given the country's current state of devolution, uncertainty arises on how local government units (LGUs) will manage to fully assume all devolved functions and whether the prescribed devolution transition period is sufficient. Through an evaluation of LGU-crafted DTPs, this study aims to establish the baseline of current (pre-Mandanas) devolved functions and capacities. The results can serve as a pivotal starting point on which to evaluate performance and progress in the phased adoption of devolved functions. Key takeaways from the exercise include (i) the high variation in LGU prioritization of devolved functions and LGU capacity, (ii) complete full devolution by 2024 is not achievable based on the self-assessment of LGUs, (iii) capacity development interventions to aid in the devolution agenda is mostly centered on manpower and training requirements. Further, the study recognizes (i) the need for a mechanism for further data collection of accurate and comprehensive baseline data for devolved functions of LGUs, (ii) the need for asymmetric decentralization strategy from national government, and (iii) the need for greater coordination and guidance from national agencies, especially on disaster risk reduction and management.
Keywords: 330; decentralization; devolution; local governance; Mandanas ruling